Evaluasi Risiko K3 dengan Pendekatan HIRARC dan Penelusuran Penyebab Utama melalui Diagram Fishbone - Septiawati, Vera; Nursagita, Chicha; Lazuardi, Rahmat; Mahfudz, Muhammad Syarqim (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Occupational Safety and Health (K3) is an important aspect in creating a conducive work environment. There are still many potential hazards that can cause work accidents and health problems. This study aims to evaluate the implementation of the K3 system at CV. X by applying the HIRARC method and fishbone analysis to identify the most significant root causes of risk. The research method applied is a qualitative descriptive approach with data collection carried out through direct observation and interviews. Risk identification is carried out according to work activities. Furthermore, Fishbone analysis is used to identify the main causes of hazards that have a high risk level. The research findings show that the identified risk levels are in the low to moderate range, with injuries to the waist, back and finger wounds as the main risks that require immediate attention. By combining the HIRARC and fishbone methods, companies can design a more focused and systematic risk control strategy.